Studies of cream seeded carioca beans (Phaseolus vulgaris L.) from a Rwandan efficacy trial: In vitro and In vivo screening tools reflect human studies and predict beneficial results from iron biofortified beans - Tako, Elad; Reed, Spenser; Anandaraman, Amrutha; Beebe, Stephen E.; Hart, Jonathan J.; Glahn, Raymond P. (Public Library of Science, 2015)
Iron (Fe) deficiency is a highly prevalent micronutrient insufficiency predominantly caused by a lack of bioavailable Fe from the diet. The consumption of beans as a major food crop in some populations suffering from Fe deficiency is relatively high. Therefore, our objective was to determine whether a biofortified variety of cream seeded carioca bean (Phaseolus vulgaris L.) could provide more bioavailable-Fe than a standard variety using in-vivo (broiler chicken, Gallus gallus) and in-vitro (Caco-2 cell) models. Studies were conducted under conditions designed to mimic the actual human feeding protocol. Two carioca-beans, a standard (G4825; 58μg Fe/g) and a biofortified (SMC; 106μg Fe/g), were utilized. Diets were formulated to meet the nutrient requirements of Gallus gallus except for Fe (33.7 and 48.7μg Fe/g, standard and biofortified diets, respectively). In-vitro observations indicated that more bioavailable-Fe was present in the biofortified beans and diet (P<0.05). In-vivo, improvements in Fe-status were observed in the biofortified bean treatment, as indicated by the increased total-body-Hemoglobin-Fe, and hepatic Fe-concentration (P<0.05). Also, DMT-1 mRNA-expression was increased in the standard bean treatment (P<0.05), indicating an upregulation of absorption to compensate for less bioavailable-Fe. These results demonstrate that the biofortified beans provided more bioavailable Fe; however, the in vitro results revealed that ferritin formation values were relatively low. Such observations are indicative of the presence of high levels of polyphenols and phytate that inhibit Fe absorption. Indeed, we identified higher levels of phytate and quercetin 3–glucoside in the Fe biofortified bean variety. Our results indicate that the biofortified bean line was able to moderately improve Fe-status, and that concurrent increase in the concentration of phytate and polyphenols in beans may limit the benefit of increased Fe-concentration. Therefore, specific targeting of such compounds during the breeding process may yield improved dietary Fe-bioavailability. Our findings are in agreement with the human efficacy trial that demonstrated that the biofortified carioca beans improved the Fe-status of Rwandan women. We suggest the utilization of these in vitro and in vivo screening tools to guide studies aimed to develop and evaluate biofortified staple food crops. This approach has the potential to more effectively utilize research funds and provides a means to monitor the nutritional quality of the Fe-biofortified crops once released to farmers.